Modern practice vectors of Chinese students adaptation to studying in Ukraine universities - Khu Zhunsi (Vasyl Stefanyk Precarpathian National University, 2017)
The paper presents the research of the current practices of adaptation of Chinesestudents to studying in Ukraine. Based on summarizing theoretical data are suggested criteriaand indicators to help experimentally determine the level of adaptability of Chinese students tothe cultural and educational environment of higher education institutions. Key words: adaptation, criteria, indicators, cultural and educational environment